Nutraceutical supplement slim reshaped colon histomorphology and reduces Mucispirillum schaedleri in obese mice - Freitas, Jessica Alves; Nehmi Filho, Victor; Santamarina, Aline Boveto; Murata, Gilson Masahiro; Franco, Lucas Augusto Moyses; Fonseca, Joyce Vanessa; Martins, Roberta Cristina; Souza, Gabriele Alves; Benicio, Gabriela; Sabbag, Isabella Mirandez; de Souza, Esther Alves; Otoch, José Pinhata; et al. (Frontiers in Microbiology, 2025)
IntroductionBioactive compounds and whole foods have emerged as promising interventions to address gut microbiota dysbiosis linked to obesity. Compounds such as berberine and coenzyme Q10 are well-recognized for their roles in managing metabolic syndrome and exerting antioxidant effects, while beet pulp, rich in fiber and antioxidants, enhances gut health through additional prebiotic benefits.MethodsThis study evaluated the effects of a nutraceutical supplement, Slim, on the modulation of gut microbiota in obese mice induced by a high-fat diet.ResultsOur results demonstrated that Slim supplementation significantly improved lipid metabolism, reshaped colon histomorphology, and decreased levels of Mucispirillum schaedleri, which were correlated with VLDL-c and triglycerides.DiscussionWe suggest these effects are driven by a duplibiotic effect, resulting from the synergistic action of the bioactive compounds.